Do patients with interictal migraine modulate pain differently from healthy controls? A psychophysical and brain imaging study. Issue 12 (December 2018) - Kisler, Lee B.; Granovsky, Yelena; Coghill, Robert C.; Sprecher, Elliot; Manor, David; Yarnitsky, David; Weissman-Fogel, Irit
Abstract : Abstract: Studies in interictal migraine show either normal or impaired pain modulation, at the psychophysical level. To date, pain modulation in migraineurs has yet to be explored concurrent with imaging methods. We aimed to investigate brain activity associated with endogenous analgesia by functional magnetic resonance imaging in attack-free migraineurs. Thirty-nine episodic migraineurs and 35 controls participated. Endogenous analgesia efficiency was assessed by the conditioned pain modulation (CPM) paradigm during functional magnetic resonance imaging. Conditioned pain modulation included 4 stimulation sequences of either test stimulus (noxious contact heat at forearm) given stand alone (Ts_alone ) or concomitant to contralateral foot immersion in cold water (Ts_conditioned ). The psychophysical CPM (Ts_conditioned minus Ts_alone ; 0-10 numerical rating scale) and related brain activity were examined. No group differences were found in the psychophysical CPM (controls: −0.52 ± 0.80; migraineurs: −0.20 ± 0.88; repeated-measures analysis of variance: P = 0.110) or related brain activity (family wise error [ P < 0.05] correction at the voxel level). Within groups, controls showed a significant CPM effect (Ts_alone : 6.15 ± 2.03 vs Ts_conditioned : 5.63 ± 1.97; P < 0.001), whereas migraineurs did not (Ts_alone : 5.60 ± 1.92 vs Ts_conditioned : 5.39 ± 2.30; P = 0.153); yet, both groups showed significant CPM-related decreased deactivation in prefrontal areas including the superior frontal gyrus and parietal regions including precuneus. The change in brain activity seems related to task demands rather than to pain reduction. The lack of group difference between migraineurs and controls in CPM and its related brain activity may result from (1) the specific CPM methodology used in this study, since migraineurs are reported to show various pain modulation efficiency for different test paradigms and/or (2) pathophysiological diversity of patients with migraine. Abstract : Attack-free migraineurs and healthy controls show similar endogenous analgesia patterns, evidenced by both psychophysical efficiency and imaging-based brain activity.